A Sub-GeV Low Mass Hidden Dark Sector of SU(2) H × U(1) X - Raymundo Ramos (SpringerOpen, 2021)
Abstract We present a detailed study of the non-abelian vector dark matter candidate W t with a MeV–GeV low mass range, accompanied by a dark photon A′ and a dark Z′ of similar masses, in the context of a gauged two-Higgs-doublet model with the hidden gauge group that has the same structure as the Standard Model electroweak gauge group. The stability of dark matter is protected by an accidental discrete Z 2 symmetry (h-parity) which was usually imposed ad hoc by hand. We examine the model by taking into account various experimental constraints including dark photon searches at NA48, NA64, E141, ν-CAL, BaBar and LHCb experiments, electroweak precision data from LEP, relic density from Planck satellite, direct (indirect) detection of dark matter from CRESST-III, DarkSide-50, XENON1T (Fermi-LAT), and collider physics from the LHC. The theoretical requirements of bounded from below of the scalar potential and tree level perturbative unitarity of the scalar sector are also imposed. The viable parameter space of the model consistent with all the constraints is exhibited. While a dark Z′ can be the dominant contribution in the relic density due to resonant annihilation of dark matter, a dark photon is crucial to dark matter direct detection. We also demonstrate that the parameter space can be further probed by various sub-GeV direct dark matter experimental searches at CDEX, NEWS-G and SuperCDMS in the near future.